Mother-offspring chemical communication and tadpole aggregation in a neotropical foam-nesting frog - Carrillo, Juan F. C.; Ortega, Zaida; Santana, Diego J.; Prado, Cynthia P. A. [UNESP] (Springer Nature, 2024)
Communication during parental care is important in the context of offspring defence and parent-offspring recognition. In aquatic environments, chemical communication is usually the most effective and plays different roles in parental behaviour in many groups of animals. Attending females of some Neotropical anurans (Leptodactylus) lead entire schools of tadpoles through the water. However, little is known about how attending females communicate with the tadpoles or whether this communication is mother-offspring specific. We therefore conducted behavioural experiments with Leptodactylus podicipinus to address these questions. Initially, we investigated how visual, tactile, and chemical stimuli from attending females affect the aggregation behaviour of tadpoles. Next, we compared the effects of the chemical stimulus from attending females with those from other conspecifics (non-attending females and males) on schooling behaviour. Finally, we tested whether tadpoles preferred to be aggregated next to familiar attending females instead of unfamiliar ones. Our results indicated that only the chemical stimulus from attending females, and not visual or tactile, increased the time that tadpoles remained aggregated. The chemical stimuli from non-attending females and males did not affect tadpoles’ behaviour. However, contrary to our expectations, we did not find a school preference for familiar attending females. Our study is the first showing that chemical stimulus is important for mother-tadpole communication in a Leptodactylus species, playing a crucial role in tadpole aggregation and attraction. Future studies including other species should address the nature of the chemical compounds and their role, if any, in kin recognition in these frogs with aquatic maternal care.
Keywords: Kin recognition; Leptodactylus; Maternal care; Parent-offspring interaction; Tadpole schooling